2014
DOI: 10.7838/jsebs.2014.19.3.125
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Demographic Analysis with IMDB User Ratings on the Recommendation of Movies

Abstract: Nowadays, overflowing data produced every second from the internet make people to be difficult to search for the useful information. That's why people have invented and developed unique tools that they get some relevant information.In this paper, the recommender system, one of the effective tools, is used and it helps us to get the useful information that we want by using demographic information to predict new items of interest. The demographic recommender system in this paper computes users' similarity using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Generally, a demographics filtering recommendation system will involve user demographic information such as gender, age, occupation, etc. to perform group clustering [8].…”
Section: Demographic Filteringmentioning
confidence: 99%
“…Generally, a demographics filtering recommendation system will involve user demographic information such as gender, age, occupation, etc. to perform group clustering [8].…”
Section: Demographic Filteringmentioning
confidence: 99%
“…In [3] the connection between user voting data and economic film characteristics such as budget and box office data has been investigated by Wasserman et al Hsu et at., using linear combination, multiple linear regression, neural networks predicted the IMDb rating from other movie's attributes using 32968 titles [4]; and In [5] Nithin et al used Logistic Regression, SVM Regression and Linear Regression to predict box office data. In [6], using available demographic information on IMDb Bae et al created a demographic movie recommender system. Ramos et al showed the distribution of votes showed a scale-free behavior [7].…”
Section: Introductionmentioning
confidence: 99%